Electrical and magnetic properties of double perovskite Y2-xCaxCoMnO6 (x = 0.1, 0.2, 0.5) - Kumar D.; Alam M.; Singh P.; Dixit S.; Ghosh A.K.; Chatterjee S. (My University, 2025)
The crystal structure, electronic, magnetic, and transport properties of the hole substituted (Ca2+) and partially B-site disordered double perovskite Y2-xCaxCoMnO6 system are studied. At room temperature, the samples demonstrated a monoclinic perovskite structure with a space group P21/n which was confirmed by Rietveld refinement of X-ray diffraction data. Ultra-violet visible analysis of these samples shows a direct band gap including gap energy near about 1.50 eV. X-ray photoemission spectroscopy measurement shows that component Co and Mn ions exist in a mixed state (Co3+, Co2+, Mn3+, and Mn4+). All samples exhibit semiconducting/insulating, and electrical conduction can be explained by Mott’s 3-D variable range hopping and small polaron hopping fitting. The magnetization numerical value decreases observed with increases in Ca concentration appears to be caused by increases in antiferromagnetic (AFM) phases. The double perovskite Y1.9Ca0.1CoMnO6 and Y1.8Ca0.2CoMnO6 show ferromagnetic transition at transition temperatures Tc~ 70 K and Tc~ 68 K, respectively. The analysis of the samples’ zero fields cooled DC magnetic susceptibility as a function of temperature reveals Griffiths-like singularity features that arise as the concentration of Ca increases in the parent system. The Griffith-like phase exists in the sample Y-site with Ca-substitution is independent of the structural disorder caused by the John–Teller active Mn3+ions in sample Y1.5Ca0.5CoMnO6. Field-dependent magnetization shows meta-magnetic behavior at low-temperature regions in Y1.9Ca0.1CoMnO6 and Y1.8Ca0.2CoMnO6. As the concentration of Ca increased from Y1.8Ca0.2CoMnO6 to Y1.5Ca0.5CoMnO6 meta-magnetic behavior disappeared. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.